교차편파 격리도를 개선한 이중선형 편파 시뉴어스 안테나의 설계 및 제작 - 김지흥; Jee-heung Kim; 유홍균; Hong-kyun Ryu; 채명호; Myung-ho Chae; 김정훈; Jung-hoon Kim; 박범준; Beom-jun Park; 박영주; Young-ju Park (한국항행학회논문지, 2018)
본 논문에서는 교차편파 격리도(XPI; cross polarization isolation)를 개선한 이중선형 편파 시뉴어스 안테나를 설계 및 제작하였다. 제안된 시뉴어스 안테나는 이중선형 편파 발생을 위해 4개의 암(arm) 방사체로 구성되며, 클로펜스타인 테이퍼(Klopfenstein taper) 구조의 광대역 마이크로스트립 발룬을 통해 급전된다. 또한 후방 반사파 감소를 위해 2단 원통형 캐비티 구조를 적용하였다. 캐비티 내부에는 반사파에 의한 성능 저하를 감소시키기 위해 허니컴 형태의 흡수체를 삽입하였다. 설계된 시뉴어스 안테나는 저대역에서의 교차편파 격리도를 개선하기 위해 최외각 암패턴과 캐비티의 림(rim) 사이에 저항을 적용하였다. 제작된 안테나는 저대역에서 교차편파 격리도가 개선되어 편파 측정을 위한 안테나로 적용 가능함을 확인하였다. In this paper, we design and fabricate a dual liner polarization sinuous antenna with improved cross polarization isolation (XPI). The proposed antenna is composed of four arm radiators for generating dual linear polarization and excited by wideband microstrip balun with Klopfenstein taper structure. Also, two-step cylindrical cavity structure is applied to reduce back radiation. Honeycomb-typed absorbing material is inserted into the cavity to reduce performance degradation by reflected wave. To enhance cross polarization isolation in low frequency band, resistors are adapted between outer arm and the rim of cavity. We confirmed that the fabricated antenna can be applied for polarization measurement due to improved XPI in the low band.